Comparing the Barriers and Facilitators of Heart Failure Management as Perceived by Patients, Caregivers, and Clinical Providers. Issue 5 (September 2019) - Trivedi, Ranak B.; Slightam, Cindie; Nevedal, Andrea; Guetterman, Timothy C.; Fan, Vincent S.; Nelson, Karin M.; Rosland, Ann-Marie; Heidenreich, Paul A.; Timko, Christine; Asch, Steven M.; Piette, John D.
Abstract : Background: Heart failure (HF) management requires the participation of patients, their significant others, and clinical providers. Each group may face barriers to HF management that may be unique or may overlap. Objective: The aim of this study was to compare the barriers and facilitators of HF management as perceived by patients, significant others, and clinical providers. Methods: Participants were recruited from a Veterans Health Administration facility. Eligible patients had a diagnosis of HF (ICD9 code 428.XX), 1 or more HF-related visit in the previous year, and a significant other who was their primary caregiver. Significant others were adults with no history of cognitive impairments caring for patients with HF. Providers were eligible if they cared for patients with HF. All participants completed semistructured interviews designed to elicit barriers to managing HF and strategies that they used to overcome these barriers. Interviews were transcribed and analyzed using latent thematic analysis, and recruitment continued until thematic saturation was attained. Results: A total of 17 couples and 12 providers were recruited. All 3 groups identified poor communication as a key barrier to HF management, including communication between patients and their significant other, between couples and providers, and providers with each other. Significant others noted that the lack of direct communication with clinical providers hindered their efforts to care for the patient. All 3 groups emphasized the importance of family members in optimizing adherence to HF self-management recommendations. Conclusions: Providers, patients, and significant others all play important and distinct roles in the management of HF. Tools to enhance communication and collaboration for all 3 and supporting the needs of significant others are missing components of current HF care.